Perception BIM Expert Towards Transition Risk to Implement BIM in IBS Projects - Shamsuddin, Shahrol Najmi; Abdul Rahim, Nur Soleha; Ibrahim, Fazdliel Aswad (Advanced and Sustainable Technologies (ASET), 2026)
The integration of Building Information Modeling (BIM) with the Industrialized Building System (IBS) has strong potential to improve productivity, coordination, and efficiency in the Malaysian construction industry. However, the transition from traditional practices to BIM-based IBS implementation involves various risks that may hinder successful adoption. This study investigates key transition risks and evaluates organizational readiness for BIM implementation in IBS projects using the Technology Readiness Index (TRI) as the guiding framework. A qualitative approach was employed through semi-structured interviews with five BIM experts from academia and industry who possess extensive experience in BIM and IBS projects. The findings reveal that financial risk is the most significant barrier, driven by high costs of BIM software, hardware, training, and specialist expertise. Management risks, particularly resistance to change and a shortage of skilled personnel, also affect adoption. Based on TRI, organizational readiness is mainly influenced by optimism and discomfort with technology, with optimism acting as a driver and discomfort as an inhibitor. Overall, the transition risk level is perceived as moderate, indicating that BIM–IBS implementation is achievable when key risks are effectively managed. This study offers practical insights to support strategic planning for BIM adoption in IBS projects and aligns with SDG 9 Industry, Innovation, and Infrastructure.